2014
DOI: 10.4314/ajtcam.v11i3.19
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Anti-Biofilm Activity of Flavonoids and Triterpenes Isolated from The Extracts of <i>Ficus Sansibarica</i> Warb. <i>Subsp. Sansibarica</i> (Moraceae) Extracts

Abstract: Background: Ficus species are used in African traditional medicine in the treatment of a wide variety of ailments and diseases such as convulsive disorder, wound healing, gonorrhea, tuberculosis, diabetes, diarrhoeal infections, dysentery, malaria and HIV. The aim of this study was to isolate the phytochemical constituents in the plant and test them for their antibacterial activity. Materials and methods: The fruits, leaves and stem bark were extracted with organic solvents and the compounds in the extracts se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 44 publications
(18 reference statements)
3
22
0
Order By: Relevance
“…Particularly, works on the antibacterial activity of individual pure compounds are relatively few. There is a small number of microbiological investigations describing the effects of some common flavonoid glycosides such as vitexin [55][56][57][58], isovitexin [59,60], vitexin 2"-O-rhamnoside [61], orientin [62,63], and isoorientin [56,60,62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, works on the antibacterial activity of individual pure compounds are relatively few. There is a small number of microbiological investigations describing the effects of some common flavonoid glycosides such as vitexin [55][56][57][58], isovitexin [59,60], vitexin 2"-O-rhamnoside [61], orientin [62,63], and isoorientin [56,60,62].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, literature data are difficult to compare due to the use of various methods for assessing antibacterial activity, different solvents, and the origin and purity of test compounds, often isolated from various plant extracts [55,57,59,60,[62][63][64][65]. Antimicrobial properties of natural chemicals were described not only by the minimum inhibitory concentration (MIC) [33,54,57,62,64,[66][67][68][69][70][71][72] and by the minimum bactericidal concentration (MBC) [72], but also by the agar well or disc-diffusion methods [59,60,63,65]. Some authors expressed results as the IC 50 or MIC 80 values [33,67,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant antimicrobial secondary metabolites are generally categorized into three broad classes, namely phenolic compounds, terpenes, and alkaloids. Numerous studies have shown that the antimicrobial activity of the plant extracts and their active compounds have the following potential: to promote cell wall disruption and lysis, induce reactive oxygen species production, inhibit biofilm formation, inhibit cell wall construction, inhibit microbial DNA replication, inhibit energy synthesis, and inhibit bacterial toxins to the host [75,85,[105][106][107][108][109]. In addition, these compounds may prevent antibacterial resistance as well as synergetics to antibiotics, which can ultimately kill pathogenic organisms (Figure 1).…”
Section: Mechanism Of Actions Of Antibacterial Bioactive Compoundsmentioning
confidence: 99%
“…Interestingly, numerous researchers have described how flavonoids cause the aggregation of multicellular composites of bacteria and inhibit bacterial growth after aggregation, which indicates that flavonoids are potent antibiofilm compounds. The bioactive flavonoids such as galangin (18), isovitexin (19), EGCG (20) and 3-O-octanoyl-epicatechin (21), as well as 5, 7, and 40-trihydroxyflavanol (22) induce pseudo multicellular aggregation of S. aureus and S. mutans [106][107][108][109]. Quorum sensing involves cell signaling molecules called autoinducers present in E. coli, Vibrio cholerae, and S. typhi, which is a notable regulatory factor for biofilm formation [126].…”
Section: Inhibition Of Biofilm Formationmentioning
confidence: 99%